Reading eye movements performance on iPad vs print using a visagraph - Alicia Feis; Amanda Lallensack; Elizabeth Pallante; Melanie Nielsen; Nicole Demarco; Balamurali Vasudevan (Bern Open Publishing, 2021)
This study investigated reading comprehension, reading speed, and the quality of eye movements while reading on an iPad, as compared to printed text. 31 visually-normal subjects were enrolled. Two of the passages were read from the Visagraph standardized text on iPad and Print. Eye movement characteristics and comprehension were evaluated. Mean (SD) fixation duration was significantly longer with the iPad at 270 ms (40) compared to the printed text (p=0.04) at 260 ms (40). Subjects' mean reading rates were significantly lower on the iPad at 294 words per minute (wpm) than the printed text at 318 wpm (p=0.03). The mean (SD) overall reading duration was significantly (p=0.02) slower on the iPad that took 31 s (9.3) than the printed text at 28 s (8.0). Overall reading performance is lower with an iPad than printed text in normal individuals. These findings might be more consequential in children and adult slower readers when they read using iPads.